2020
DOI: 10.1101/2020.09.24.311712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Surface condensation of a pioneer transcription factor on DNA

Abstract: In the last decade, extensive studies on the properties of non-membrane-bound compartments in the cellular cytoplasm have shown that concepts in phase separation drawn from physical chemistry can describe their formation and behaviour1–4. Current evidence also suggests that phase separation plays a role in the organization inside the cell nucleus5–8. However, the influence and role of DNA on the physical chemistry of phase separation is not well understood. Here, we are interested in the role of interactions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 81 publications
7
28
0
Order By: Relevance
“…Morin et al, used the Brunauer-Emmett-Teller theory (45) for multilayer adsorption to explain their results. Taken together, it follows that preferential binding of multivalent ligands to scaffolds in dense phases, this work and that of Ghosh et al, (26) and Espinosa et al, (27), and adsorption of scaffolds to surfaces (46, 47) as shown by Morin et al, (44) can lead to similar effects in terms of lowering the saturation concentrations of scaffold macromolecules. Therefore, we propose that the stabilization of condensate formation via surface interactions derives from preferential adsorption of dense phases through spacer-surface interactions and / or enhancing of sticker-sticker crosslinks.…”
Section: Discussionsupporting
confidence: 75%
“…Morin et al, used the Brunauer-Emmett-Teller theory (45) for multilayer adsorption to explain their results. Taken together, it follows that preferential binding of multivalent ligands to scaffolds in dense phases, this work and that of Ghosh et al, (26) and Espinosa et al, (27), and adsorption of scaffolds to surfaces (46, 47) as shown by Morin et al, (44) can lead to similar effects in terms of lowering the saturation concentrations of scaffold macromolecules. Therefore, we propose that the stabilization of condensate formation via surface interactions derives from preferential adsorption of dense phases through spacer-surface interactions and / or enhancing of sticker-sticker crosslinks.…”
Section: Discussionsupporting
confidence: 75%
“…The causal relevance of Pol II phosphorylation is supported by the application of chemical inhibitors of Pol II phosphorylation, which induces changes in cluster morphology and cluster number that are in line with predictions from our lattice simulations. In combination with previous work on Pol II liquid phase behavior 13,14 and studies showing condensation of transcription factors by wetting of DNA in vitro 23,24 , our findings in zebrafish, an embryonic model system, suggest that similar liquid phase wetting of chromatin might also occur in vivo.…”
Section: Introductionsupporting
confidence: 87%
“…11). This behavior is typical of liquid phase condensation on a surface, also called wetting 24 . To confirm that the simulations exhibit surface-mediated condensation, we demonstrate another key behavior: the size of clusters is controlled by the amount of available surface (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…While our focus is on membranes, prewetting can occur on other interesting biological surfaces. Phase separation has been proposed to play prominent roles in transcriptional regulation (47, 48), where DNA has been proposed to act as a one-dimensional ‘surface’ for prewetting (49).…”
Section: Discussionmentioning
confidence: 99%